Expression of let-7 family as a survival biomarker for lung cancer: A meta-analysis - Azizi, Faezeh; Aliakbari, Fereshteh; Zolghadr, Zahra; Hosseini, Reza; Hashemi, Reza (Archives of Men’s Health, 2018)
Introduction: Lung cancer is the most common cancer among men around the world. Today, by evaluating the expression of microRNA biomarkers, cancer cells can be detected in specific tissues. However, it’s still controversy that the expression of let-7 in the prognosis of patients with lung cancer is informative. Material and Methods: A meta-analysis was performed by searching Google Scholar, PubMed, Scopus, Web of Science, IranMedex, MEDLIB, IranDoc and Scientific Information Database(SID). All data were extracted from articles comparing prognosis in patients with lung cancer having low expression of let-7 with those having high expression. Pooled hazard ratios (HRs) and corresponding 95 % confidence intervals (CIs) were calculated. Subgroup analyses were conducted for ethnicity. Results: A total of 1,370 cases of lung cancer were involved for this meta-analysis. The HR of low let-7 expression was 1.32 (95 % CI 0.68–2.58). A subgroup analysis was performed on ethnicity; combined HR was 1.56 (95 % CI 0.52–4.62) for Asians and 1.08 (95%CI 0.42–2.74) for non-Asians. Conclusion: There was no significant relationship between the expression of let-7 and lung cancer, let-7 might be a biomarker in Asian patients with favourable prognosis. Furthermore, with large-scale investigations, useful prognostic microRNA biomarkers in the diagnosis, treatment and follow-up could be detected.